Value For Money Audit Suatu Instrumen Alternatif untuk Menciptakan Akuntabilitas Publik Pemerintah Daerah - Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2003)
Regional autonomy has been running for almost two years, a lot of comments about the success of regional autonomy, both positive and negative. Comments indeed very necessary, but the main thing is how to make regional autonomy which is the people's demands to be more perfect and more perfect. One measure of the success of decentralization is the creation of